Pengaruh Kompetensi dan Sarana Prasarana terhadap Kualitas Pelayanan Kantor Dinas Catatan Sipil Kabupaten Sorong Selatan - Maryen, Andrey; Sapari, Lili Sarce Joi; Kehek, Oktofina (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was to analyze the influence of competence and infrastructure on the quality of service of the Civil Registry Office of South Sorong Regency. Sampling was carried out using a population sample, namely all populations were involved to become a sample of 30 respondents. The type of research used was quantitative with multiple linear regression analysis by conducting a T test, F test, and determination coefficient test. From the results of the calculation using multiple linear regression analysis, the regression equation Y = 7.854 + 0.087X1 + 0.934X2 was obtained. Based on the results of the analysis and discussion, it was concluded that infrastructure had a significant effect on the quality of service of Civil Registry Office Employees of South Sorong Regency, while competence did not affect the quality of service, but simultaneously together with infrastructure had a significant effect on the quality of service of Civil Registry Office Employees of South Sorong Regency.